Robotics Integration in Manufacturing: Case Study of South Korea - Na-yeon, Han (Asian Journal of Computing and Engineering Technology, 2024)
Purpose: Aim of the study was to analyze the robotics integration in manufacturing: case study of South Korea. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Robotics integration in South Korean manufacturing has revolutionized industry, boosting efficiency, productivity, and global competitiveness. Key sectors like automotive and electronics have seen significant benefits, including reduced labor costs, enhanced product quality, and faster production cycles. This advancement has also spurred innovation in robotics technology, making South Korea a leader in this field globally. Unique Contribution to Theory, Practice and Policy: Diffusion of innovations theory, technology acceptance model (TAM) & network externalities theory may be used to anchor future studies on robotics integration in manufacturing: case study of South Korea. Develop practical guidelines for integrating robotics into diverse manufacturing sectors. South Korea's experience underscores the importance of sector-specific customization and scalability in robot deployment. Establish regulatory frameworks that balance innovation with safety and ethical considerations in robotic manufacturing. South Korea's proactive regulatory policies support industry standards for robot safety and data privacy, fostering a conducive environment for technological innovation.